Health literacy in an Israeli elderly population - Michal Hochhauser; Michael Brusovansky; Maria Sirotin; Katerina Bronfman (BMC, 2019)
Abstract Background Health literacy is important for patients' comprehension of the health and medical messages conveyed to them and their meaning for them so that they can better manage their health. The aim of the study was to examine the level of health literacy within the elderly population. The hypothesis was that health literacy would be inadequate, and related to demographic variables. Method Sixty men and women over the age of 65 who volunteered to participate in the study completed a 13-item health literacy questionnaire. Results Overall, the level of health literacy among the participants was mostly inadequate. They reported difficulty in reading medical material in Hebrew and understanding the doctor, thus requiring assistance (20%); difficulty in reading medical documents, completing medical forms and understanding medical terms; difficulty in reading the leaflet attached to medications (33%), test results (40%) and medical information written in English (66%) and difficulty searching the internet for information (53.3%). The level of health literacy was associated with education while the best profile for adequate health literacy was for those who spoke Hebrew and completed secondary education. Conclusions Medical teams have an obligation to be alert and attentive to the level of health literacy of elderly patients and to modify communication and information to an accommodating degree, so that elderly patients can better manage their health.